2021
DOI: 10.1155/2021/2365399
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Anthropometry Indices and Serum Concentrations of Gamma-Glutamyl Transferase, Alkaline Phosphatase, Alanine Aminotransferase, and Aspartate Aminotransferase

Abstract: Background. Nowadays, metabolic syndrome (MetS) has become a great public health crisis that threatens too many lives worldwide. Many previous studies have been investigated the association between MetS and anthropometric indices. This study is aimed at investigating the association between anthropometric indices with gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). We were using data from a large population-based cohort of seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A recent study by Sobhani et al. found that BMI was a consistent predictor of triglycerides and increased hepatic enzymes, although the relevance of NC was not indicated ( 44 ). Other recent studies have reported that obesity is involved with microvascular disease progression, including retinopathy in T2D ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Sobhani et al. found that BMI was a consistent predictor of triglycerides and increased hepatic enzymes, although the relevance of NC was not indicated ( 44 ). Other recent studies have reported that obesity is involved with microvascular disease progression, including retinopathy in T2D ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the baseline POCM examination, calibrated devices and standardized questionnaires were utilized by expert personnel (cardiologists, general practitioners, nurses, and dietitians) to collect all the data/information required by the study protocol [ 15 , 20 , 23 , 24 ]. Weight (kilograms), waist and hip circumference (centimeter), height (meters), BMI (kg/m 2 ), and anthropometric measurements were calculated using US National Institutes of Health protocols [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serum liver enzymes are considered to be important markers for assessing liver injury in clinical work. In some studies, it has been found that some serum liver enzymes can also be used as indicators affecting clinical outcomes in PD patients, including ALT, AST, ALP, and GGT [ 5 ].…”
Section: Liver Enzymesmentioning
confidence: 99%